2003
DOI: 10.1080/10284150310001624192
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Genetic Analysis of Ventral Midbrain and Liver Iron in BXD Recombinant Inbred Mice

Abstract: Male and female mice from 15 of the BXD/Ty recombinant inbred strain panel were examined for regional brain and liver iron content. Brain regions included medial prefrontal cortex, nucleus accumbens, caudate-putamen and ventral midbrain. Our focal tissue was the ventral midbrain, containing the ventral tegmentum and substantia nigra. This area contains the perikarya of the dopamine neurons that project to nucleus accumbens and caudate-putamen. Genetic correlations between ventral midbrain and liver iron conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 39 publications
3
52
1
Order By: Relevance
“…4 A and B). Interestingly, a prior analysis has revealed that these (and other) DA-related phenotypes are associated with midbrain iron levels (25). Consistent with these findings, the GK mSERT haplotype associates significantly with elevated iron levels in both the region of DA cell bodies (ventral midbrain) and DA terminal fields (caudateputamen) (Fig.…”
Section: In Silico Identification Of Phenotypes Influenced By Slc6a4 supporting
confidence: 75%
“…4 A and B). Interestingly, a prior analysis has revealed that these (and other) DA-related phenotypes are associated with midbrain iron levels (25). Consistent with these findings, the GK mSERT haplotype associates significantly with elevated iron levels in both the region of DA cell bodies (ventral midbrain) and DA terminal fields (caudateputamen) (Fig.…”
Section: In Silico Identification Of Phenotypes Influenced By Slc6a4 supporting
confidence: 75%
“…This is an intriguing QTL as the DAT is one of the main targets for psychostimulant action. Another QTL potentially related to dopamine system function, Vmbic10 (ventral midbrain iron content) also maps at 24 cM on Chr 11 (Jones et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative trait analysis, using panels of BxD recombinant inbred (RI) mice, continues to be one of the leading methods for the study of genes involved in complex neurobehavioral traits. The BxD series has been used to nominate and map QTL that contribute to a wide variety of complex traits including behavioral, pharmacological, neurochemical and neuroanatomical phenotypes (Erwin et al, 1997;Garlow et al, 2005Garlow et al, , 2006Jones et al, 1999Jones et al, , 2003Gora-Masalak et al, 1991;Belknap et al, 1992;Zhang and Gershenfeld 2003). The major goal of this study is to conduct quantitative trait analysis of CART expression in hypothalamus, by utilizing the BxD series of RI mice.…”
Section: Introductionmentioning
confidence: 99%
“…Fe, Cu, and Zn in the brain are of widespread neurobiological importance as they contribute to a diverse set of biochemical processes, including energy metabolism (Fe, Cu), antioxidant defense (Cu, Zn), myelination (Fe), DNA synthesis (Fe, Zn), and neurotransmitter synthesis (Fe, Cu) (Linder and Hazegh-Azam, 1996;Beard, 2003;Frederickson et al, 2005). Deficiencies of these metals are thus detrimental to brain function; yet, they must be regulated strictly because they are toxic when in excess (Levenson, 2005).…”
Section: Introductionmentioning
confidence: 99%